Synthesis of Poly(Hexamethylene Succinate-Co-Ethylene Succinate) Copolymers With Different Physical Properties and Enzymatic Hydrolyzability by Regulating the Ratio of Monomer - Li, Menglu; Jing, Jing; Su, Tingting (Frontiers in Bioengineering and Biotechnology, 2022)
Poly(hexylene succinate) (PHS), poly(ethylene succinate) (PES) and their random copolyesters, poly(hexylene succinate-co-ethylene succinate) ((P(HS-co-ES)), were synthesized by melt polycondensation. Simply varying the ratios of HS/ES afforded control over the copolymer crystallinity, thermal and mechanical properties, wettability and enzymatic hydrolyzability as shown by X-ray diffraction (XRD), differential scanning calorimetry (DSC), tensile tests, and water contact angle (WCA) measurements. The enzymatic hydrolysis rates of all prepared copolyesters were higher than those of the corresponding homopolyesters. The hydrolysis rates were affected by the crystallinity, melting temperature and hydrophobicity of the copolyesters, and therefore, the degradation rates could be tuned along with the ES content. The library of copolymers prepared here with tunable degradation rates, ranging from HS-enriched to ES-enriched copolyesters, is promising for variety of different applications. The P(HS-co-ES51) copolyester that did not fully degrade is particularly promising for use in long-term storage applications, whereas P(HS-co-ES13) and P(HS-co-ES76) that rapidly degrade are good for use in very short-term applications.